Značilnosti časovnega pojavljanja nezgod pri nepoklicnem gozdnem delu - Medved, Mirko (Gozdarski vestnik, 2007)
Non-professional work in forests is traditional in Slovenia. There are frequent accidents and little data on them. Only police reported serious and fatal accidents are systematically monitored by the Slovenian forestry institute. The characteristics of accident occurrence for four 6-years long periods from 1981 to 2004 are analysed. Important societal changes, reorganisation of forestry and the legislation of safety and health at work during four periods should influence accident occurrence in non-professional work. Characteristics of accident occurrence by seasons, months, days and hours are compared with contingency tests for four 6-year periods. There is nosignificant difference between occurrence of fatal (N=302) and serious accidents (N=382). For further comparisons all accidents regardless seriousness were analysed together, where only occurrence by months was significantly different in the compared periods. The hourly and daily distribution of accidents are very similar for all periods. During the week there were significantly fewer accidents in the last period on Sundays. Despite societal and other changes which have occurred during the 24 years studied, working habits and safety are practically the same as 24 years ago. There were 16 fatal accidents yearly during the first period (1981-1986) and 13 during the last period (1994 - 2004). Characteristics of accident occurrence show that changes in society, forestry and stricter legislation didnot significantly influence improvement of safety. The different ministerial policies should be harmonised and strategy prepared for safety improvement in non-professional forest work and other activities of high risk.
Keywords: delo v gozdu; nepoklicno delo; nezgode; Slovenia; Slovenija